2011
DOI: 10.1126/science.1199682
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Clonal Reproduction Through Seeds

Abstract: Cloning through seeds has potential revolutionary applications in agriculture, because it would allow vigorous hybrids to be propagated indefinitely. However, asexual seed formation or apomixis, avoiding meiosis and fertilization, is not found in the major food crops. To develop de novo synthesis of apomixis, we crossed Arabidopsis MiMe and dyad mutants that produce diploid clonal gametes to a strain whose chromosomes are engineered to be eliminated after fertilization. Up to 34% of the progeny were clones of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 6 publications
3
97
0
1
Order By: Relevance
“…A virtually identical copy of the insertion has been found in every OP D. pulex tested. Moreover, abrogation of Rec8 function, which could plausibly result from the retroelement insertion, is also known in other species to result in phenotypes similar to those seen in OP D. pulex (32)(33)(34)(35)(36)(37). The finding that the Rec8 insertion and portions of three other chromosomes (8) are all strongly associated with OP is concordant with results from other systems, in which mutation of just a small number of loci is required to induce a switch from sexual to asexual reproduction.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A virtually identical copy of the insertion has been found in every OP D. pulex tested. Moreover, abrogation of Rec8 function, which could plausibly result from the retroelement insertion, is also known in other species to result in phenotypes similar to those seen in OP D. pulex (32)(33)(34)(35)(36)(37). The finding that the Rec8 insertion and portions of three other chromosomes (8) are all strongly associated with OP is concordant with results from other systems, in which mutation of just a small number of loci is required to induce a switch from sexual to asexual reproduction.…”
Section: Discussionsupporting
confidence: 76%
“…Although mutations to multiple loci are required to induce obligate asexuality in A. thaliana (32,33), it is theoretically possible that Rec8 abrogation alone is sufficient to induce pseudomeiosis in D. pulex, because loss of Rec8 function affects each of the three processes modified during pseudomeiosis (HR, sisterchromatid orientation, and cohesion). Although we know of no examples of rec8 mutants that specifically result in successful clonal propagation, mutant or biochemical studies in Schizosaccharomyces pombe and other organisms (34)(35)(36)(37) are consistent with the idea that loss of Rec8 function could be sufficient to abrogate meiotic sister chromatid cohesion and HR, and to orient sister chromatids to opposite poles.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of sex-lethal transmission after haploidization should add useful information on the function and regulation of these genes. These findings add to our previous work in which we demonstrated that haploids can be used to rapidly generate mapping populations 46 , chromosome substitution lines 47 , parental lines for reverse breeding 47 and for engineering clonal reproduction through seeds 48 . Finally, like in haploid yeast, it is possible to measure meiotic crossover and gene conversion using Arabidopsis haploids 49 and to study meiotic recombination events in the absence of a homologous partner during haploid meiosis 50 .…”
Section: M1 Haploidsmentioning
confidence: 55%
“…This triple mutant, called MiMe (Mitosis instead of Meiosis) combines mutants in the omission of second division 1 (Osd1), Atspo11-1, and Atrec8 genes and produces viable diploid gametes that are genetically identical to their mother (D'Erfurth et al 2009). The MiMe and dyad mutants have both been used in an attempt to engineer apomixis in Arabidopsis as a proof of concept (Marimuthu et al 2011). Instead of replicating parthenogenesis, MiMe and dyad mutants were crossed with an Arabidopsis line that contains a manipulated centromerespecific histone (CENH3), which has previously been demonstrated to cause genome elimination (Ravi and Chan 2010).…”
Section: Mutants That Develop Embryo Sacs Without Meiosis (Apomeiosismentioning
confidence: 99%